Improving efficiency in meat production. Issue 3 (18th April 2016) - Brameld, John M.; Parr, Tim
Abstract : Selective breeding and improved nutritional management over the past 20–30 years has resulted in dramatic improvements in growth efficiency for pigs and poultry, particularly lean tissue growth. However, this has been achieved using high-quality feed ingredients, such as wheat and soya that are also used for human consumption and more recently biofuels production. Ruminants on the other hand are less efficient, but are normally fed poorer quality ingredients that cannot be digested by human subjects, such as grass or silage. The challenges therefore are to: (i) maintain the current efficiency of growth of pigs and poultry, but using more ingredients not needed to feed the increasing human population or for the production of biofuels; (ii) improve the efficiency of growth in ruminants; (iii) at the same time produce animal products (meat, milk and eggs) of equal or improved quality. This review will describe the use of: (a) enzyme additives for animal feeds, to improve feed digestibility; (b) known growth promoting agents, such as growth hormone, β-agonists and anabolic steroids, currently banned in the European Union but used in other parts of the world; (c) recent transcriptomic studies into molecular mechanisms for improved growth efficiency via low residual feed intake. In doing so, the use of genetic manipulation in animals will also be discussed.